New therapy options for amyotrophic lateral sclerosis. (October 2013) - Gordon, Paul; Corcia, Philippe; Meininger, Vincent
Abstract : Introduction: Amyotrophic lateral sclerosis (ALS) is a rapidly progressing neurodegenerative disease leading almost irrevocably to paralysis and death within 5 years after the first symptoms. Since the approval of riluzole, all other therapeutic trials have been negative, including many that followed hopeful preclinical and early clinical data. New approaches are needed to uncover effective treatments for this still-devastating disease. Areas covered: The review summarizes the current approaches to clinical drug development in ALS. It focuses on several new trials listed on PubMed Central or the National Institutes of Health online trial registry. New targets for therapeutic intervention in ALS include skeletal muscle, energetic metabolism and cell replacement. Two different approaches are directed at muscle: interventions that influence proteins near the neuromuscular junction such as Nogo-A; in contrast to drugs pointed toward disease physiology, therapies that directly increase strength. Other trials are evaluating nutritional interventions. Current cell therapy strategies utilize various types of stem cells to study disease pathophysiology, support neurons or surrounding cells through gene therapy or release of neurotrophic factors, or directly replace cells. The review includes a section on known genetic influences in ALS and future directions for the field. Expert opinion: These new interventions have important implications for the direction of ALS research. Investigators are focusing less on physiological mechanisms inside the neuron, a process that has proved unfruitful for nearly two decades, and more on concepts that have not been examined previously. These studies will surely add to the overall understanding of ALS. Future research will test ways to reduce gene expression in those with known mutations, as well as means to reduce the spread of aggregated protein.